Online Mindfulness Intervention for Inflammatory Bowel Disease: Adherence and Efficacy - Forbes, Leila; Johnson, Susan K. (Frontiers in Psychology, 2022)
The impact of stress and other psychological variables on Inflammatory Bowel Disease (IBD) prognosis, treatment response, and functional level is well-established; however, typical IBD treatment focuses on the physiological pathology of the disease and neglects complementary stress-reducing interventions. Recent pilot studies report the benefits of mindfulness-based interventions in people living with IBD, but are limited by small sample sizes. Recruitment challenges to in-person studies may be in part due to the difficulty IBD patients often have adhering to fixed schedules and travel as a result of IBD symptoms such as pain, fatigue, and incontinence. The current study aimed to address this barrier by offering participants access to online mindfulness training, allowing individuals to engage with intervention materials to fit their own schedule. Online mindfulness programs have gained popularity in recent years, as they increase access and flexibility and decrease cost to the user; however, the dropout rate tends to be high. The current study compared the rate of adherence and efficacy of mindfulness training as a function of level of support: self –guided versus supported. Analysis revealed no significant difference in the benefits received between participants in the two groups; however, a significant difference group (X2= 15.75; p= .000, r= .38) was found in terms of rate of completion, with 44.1% of the supportive group completing the protocol compared to 11.7% of the self-guided. Common challenges to meditation were measured, but did not significantly predict adherence to the intervention, and experience of these challenges did not significantly change (increase or decrease) over the duration of the study. Implications of the current research, future directions for the use of mindfulness-based intervention for IBD patients, and a discussion of methodological considerations are provided.